The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1002/clc.4960271109
|View full text |Cite
|
Sign up to set email alerts
|

Impact of left ventricular diastolic function on exercise capacity in patients with chronic mitral regurgitation: An exercise echocardiography study

Abstract: SummaryBackground: Mitral regurgitation (MR) is known as one of the most frequent causes of heart failure and sudden death. In spite of increasing prevalence of MR, there have been no available data on cardiac determinants of exercise capacity in patients with chronic MR.Hypothesis: This study aimed to investigate cardiac determinants of exercise capacity in patients with chronic MR.Methods: We consecutively enrolled 32 patients (11 men, mean age: 44 ± 14 years) who had greater than moderate MR with normal lef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Indeed, FC is affected by LV characteristics, but not by LV systolic function, as all end-systolic LV indices showed no association to FC. Conversely, diastolic function is a major FC determinant (10,11,19), now shown to also strongly influence FC in organic MR (7). High E/E= ratio marks diastolic dysfunction with higher LV filling pressures (9,20) independent of MR (21).…”
mentioning
confidence: 95%
“…Indeed, FC is affected by LV characteristics, but not by LV systolic function, as all end-systolic LV indices showed no association to FC. Conversely, diastolic function is a major FC determinant (10,11,19), now shown to also strongly influence FC in organic MR (7). High E/E= ratio marks diastolic dysfunction with higher LV filling pressures (9,20) independent of MR (21).…”
mentioning
confidence: 95%
“…16,17 It is well known that functional capacity of patients with chronic valvulopathy is dependant on diastolic function and a careful interpretation of echocardiographic measurements of heart function in those patients is required. 18 Similarly, recent studies analyzing right ventricle contractile function in children with heart failure secondary to pulmonary hypertension and congenital heart disease resulting in right ventricle pressure/volume overload or after corrected tetralogy of Fallot, failed to demonstrate a correlation between brain natriuretic peptide and ejection fraction. [19][20][21] Use of troponin to identify overt or underlying ventricular dysfunction has been well described in numerous conditions such as in acute myocardial infarction, heart failure, and septic shock and during multiorgan failure.…”
Section: Discussionmentioning
confidence: 95%
“…Later, Skaluba and Litwin indicated an association between tissue Doppler diastolic parameter E/Ea and exercise capacity in 121 patients without evidence of ischemic heart disease [16]. Kim et al [17] reported a potential role of LV diastolic function as a determinant of exercise capacity in 32 patients with mitral regurgitation. Furthermore, Wong et al [18] reported that LV diastolic function can predict exercise limitation in 119 patients with normal EF.…”
Section: Diastolic Function and Exercise Capacitymentioning
confidence: 97%
“…However, previous studies suggest that LV diastolic function before stress can predict exercise capacity in individuals with non-ischemic heart disease. Kim et al [17] demonstrated that pre-exercise diastolic function showed a significant correlation with exercise duration in patients with mitral regurgitation using echocardiography. Grewal et al also documented that the grade of diastolic function was strongly associated with a decreased exercise capacity in non-ischemic patients [19].…”
Section: Diastolic Function and Exercise Capacitymentioning
confidence: 98%
See 1 more Smart Citation